Evaluation of fibroblast activation protein-specific PET/CT in a patient with post-COVID pneumonitis - Musameh, Khaled; O'Brien, Shane; Mehboob, Roshane; Butler, Thomas; Cunningham, Zara; Buckley, Carol; Atzinger, Armin; Kuwert, Torsten; Mitchell, Patrick; Donnelly, Seamas C. (Respirology Case Reports, 2024)
Coronavirus disease 2019 (COVID-19) often leads to a spectrum of pulmonary complications, including interstitial lung disease (ILD) with the potential for fibrotic sequelae. Assessing the presence of ongoing active inflammation versus established residual fibrosis as a result of lung parenchymal injury and repair in these patients is a clinical challenge. Better understanding of the disease process is crucial for guiding appropriate therapeutic strategies. We aim to investigate the use of positron emission tomography / computer tomography (PET/CT) scans and their role in diagnosing interstitial pneumonitis (IP) post COVID infections.
CRIS-Team Scopus Importer:2024-09-20
Keywords: coronavirus disease 2019; interstitial lung disease; progressive Fibrosing interstitial lung disease